Safety Climate in a Revenue Collecting Agency: A Case Study on Lembaga Hasil Dalam Negeri Malaysia - Aina Hartini, Hussin (2009)
In an opening speech of a seminar on Occupational Safety and Health (OSH) on 27 January 2007 at Malaysia Airport Holding Berhad's Headquarters in Subang, it was reported that the Social Security Organization's total payment in respect of temporary and permanent disablement benefits, dependant's benefits, funeral benefits, allowance, medical benefits, invalidity pension and survivor's pension totaled some 890 million in 2005. Based on those figures and working on the assumption that the true costs of poor OSH performance can be 5 to 10 times the direct costs, the National Institute of Occupational Safety and Health (NIOSH) predicted that Malaysia will incur an intangible loss of an estimated RM5 billion due to accident involving workers by the year 2020 if nothing is done to develop a safety culture among the nation's workforce. Thus, key among the various activities of the Human Resources Management (HRM) function now is the role of ensuring a safe and healthy workplace is provided for employees. This task is not only due to economic reasons but also as required by legislations on safety and health which had been introduced aggressively and regularly since 1970s. Leaders play a significant role in HRM and must always be regarded as the human resource caretaker at all times regardless whether they are the top guns, or the middle management or even supervisors. The increase in HRM focus which now includes challenges to change the perception of an organization on occupational safety and health, demands understanding on safety culture and safety climate to enable transformation of safety practices positively. This study which is exploratory in nature is conducted at Lembaga Hasil Dalam Negeri Malaysia (LHDNM) with the objective to gauge the safety climate of LHDNM based on several determinants namely awareness, perception, management commitment and occupational hazard. The study was conducted through a qualitative approach by using multi methods that were tailored to answer the research questions. The main data collection method involves interviewing 15 individual respondents and focus group of 3 (three) respondents. The samples were taken from the Klang Valley population which represents various factors such as working level and job specification. As to strengthen the findings, data from telephone interviews with officers from relevant organizations, information from primary, self reported and secondary data were also analyzed to give a more valid and reliable result to the study. The findings indicated that the awareness level is generally low with all the respondents having none or extremely limited knowledge on the Occupational Safety and Health Act (OSHA) 1994 [Act 5 141. Consequently, OSH is also wrongly perceived by the employees with them having inaccurate perceptions on the concepts of OSH. The lack of knowledge and understanding among management, human resource personnel and administrators also contribute to their weak commitment towards OSH implementation and enforcement. The research reveals that the two main occupational hazards faced by LHDNM workforce are psychosocial hazard in the form of threats and heavy workload leading to stress and traveling hazard leading to motor vehicle accident risks. On the whole, introduction of OSH as a platform to a safer and healthier work environment that will ensure the welfare of staff is safeguarded as practicable as possible is very much needed and anticipated at LHDNM.